The Dark Tetrad and mating effort as predictors of propensity for sexual coaxing and coercion across different potential victim-perpetrator relationships - Koscielska, Roksana (2017)
The Dark Tetrad (narcissism, Machiavellianism, psychopathy, and sadism) and mating effort were assessed in relation to sexual coaxing and coercion across three victim-perpetrator relationships (neighbour, ex-partner, current romantic partner). Community individuals (N = 151) voluntarily participated in an online survey. While the relationship status had no effect on sexual coercion, propensity for sexual coaxing was highest for a romantic partner, followed by an ex-partner, followed by a neighbour. Multiple regression analyses indicated that mating effort made a unique contribution in neighbour and ex-partner sexual coaxing conditions, and the Dark Tetrad and mating effort, as a set, significantly predicted sexual coaxing and coercion across all victim-perpetrator relationships, even when the influence of gender, sexual experience, criminality, and the HEXACO personality traits was considered. The current study supports previous research; the shared variance of the Dark Tetrad traits and mating effort appears to predict sexual coaxing and coercion while the individual traits provide little incremental value.